The Role of Person-Environment Fit in Mediating The Effects of Company Culture toward Employeesâ Turnover Intention in PT. Berca Hardayaperkasa - Nursanti, Tinjung Desy; Masruroh, Masruroh; Maharani, Andela Putri (Bina Nusantara University, 2015)
The purpose of this study was to investigate the mediating effect of person-environment fit on theÂ relationship between organizational culture and staff turnover intention. Data were obtained from permanentÂ employees who were working in unit business at PT.Berca Hardayaperkasa (n = 75). This research method isÂ explanatory survey. This type of research is associative. The analysis used in this study is a path analysis. TheÂ results indicate that the organizational culture has a significant influence to the staff turnover intention andÂ person-environment fit has a significant mediating influence on the relationship between organizational cultureÂ with staff turnover intention.